Penerapan Digital Marketing pada E-commerce dan Media Sosial dalam Upaya Peningkatan Penjualan Produk PT Behaestex - Fanza Shofaun Nafsi; Yanda Bara Kusuma (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
Technological developments are developing very rapidly, thus presenting various challenges, especially in the trade sector. Digital marketing as a marketing tool that has a huge impact. The rapid growth of e-commerce has become an opportunity that businesses should not miss to market their products. Limited market reach has often been an obstacle for some companies. Because social media is often thought of as the publication of personal activities, in fact it can be part of a marketing strategy. This study aims to find out the reasons for implementing digital marketing in increasing sales of PT Behaestex products. This study uses a descriptive method with a qualitative approach, and data sources are taken from interviews and direct observation. The results showed that PT Behaestex's digital marketing implementation, especially e-commerce and social media was a fairly effective promotional tool marked by a significant increase in sales volume.